Development and characterization of a line with substitution of chromosome 4B of wheat Triticum aestivum L. on chromosome 4Hmar of wild barley Hordeum marinum ssp. gussoneanum (4x) - L. A. Pershina; N. V. Trubacheeva; V. K. Shumny; E. D. Badaeva (Вавиловский журнал генетики и селекции)
Introgressive hybridization is the main method of broadening the genetic diversity of bread wheat. Wild barley Hordeum marinum ssp. gussoneanum Hudson (2n = 4x = 28) has useful agronomical traits, such as high resistance to stress factors, that could be a potential source of new genes for bread wheat improvement. This study aimed to evaluate the possibility of introgression of H. marinum chromosomes into the genome of bread wheat using an incomplete amphiploid H. marinum ssp. gussoneanum (4x)–T. aestivum (Pyrotrix 28) (2n = 54) carrying the cytoplasm of wild barley. For this purpose, we crossed the line of bread wheat variety Pyrotrix 28 with an incomplete amphiploid, and then selected cytogenetically stable 42chromosome plants with a high level of fertility in hybrid progeny. Genomic in situ hybridization (GISH) revealed a pair of H. marinum chromosomes in the genome of these plants. C banding analysis confirmed that bread wheat chromosome 4B was replaced by wild barley chromosome 4Hmar. SSR markers Xgwm368 and Xgwm6 confirmed the absence of chromosome 4B, and EST markers BAWU808 and BAW112 identified chromosome 4Hmar in the genome of the isolated disomic wheatbarley substitution line. The study of this line showed that the substitution of chromosome 4B with chromosome 4Hmar resulted in a change of some morphological traits. It included intense anthocyanin coleoptile coloration, specific for H. marinum, as well as a lack of purple coloration of the ears in the leaf sheath, specific for Pyrotrix 28. Line 4Hmar(4B) showed increased performance for several traits, including plant height, number of spikes and tillers per plant, spikelet and grain number in the main spike, grain number per plant, but it had decreased values of 1000grain weight compared to wheat. Cytogenetic stability and fertility of line 4Hmar(4B) indicated a high compensation ability of barley 4Hmar for wheat chromosome 4B and confirmed their homeology.